Exploring the Impact of Work-Life Balance on Organizational Citizenship Behavior: The Role of Psychological Well-Being as a Mediator - Redi Alamsyah; Lusi Olis Vera; Ummu Artha Tsary Rumalessin (Petra International Journal of Business Studies, 2025)
This study examines the influence of Work-Life Balance on Organizational Citizenship Behavior (OCB), with Psychological Well-being as a mediating variable, among online tutorial tutors supervising academic writing at the Faculty of Economics, Universitas Terbuka, during the 2024/2025 semester. A quantitative approach, utilizing a cross-sectional survey design, was employed in this research. The population consisted of all tutors supervising academic writing, with a sample size of 100 online tutorial tutors. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that work-life balance has a positive and significant effect on both Organizational Citizenship Behavior and Psychological Well-Being. Furthermore, Psychological Well-Being also positively and significantly influences Organizational Citizenship Behavior. Notably, Psychological Well-Being is found to mediate the relationship between Work-Life Balance and Organizational Citizenship Behavior. Practically, these findings imply that organizations in the education sector adopt policies that support Work-Life Balance. Such policies may enhance tutors' Psychological Well-Being, which fosters Organizational Citizenship Behavior that aligns with organizational goals. Theoretically, this study introduces Psychological Well-Being as a mediator in the relationship between Work-Life Balance and Organizational Citizenship Behavior, thereby enriching the understanding of the mechanisms connecting the two constructs.